1999
DOI: 10.1021/ja984346+
|View full text |Cite
|
Sign up to set email alerts
|

A “Hydrat-Ion” Spine in a B-DNA Minor Groove

Abstract: The minor groove hydration spine is a key feature of the crystal structure of the B-DNA dodecamer duplex [d(CGCGAATTCGCG)]2. At the floor of the groove, water molecules bridge bases from opposite strands by hydrogen bonding to N3 and O2 atoms of adenine and thymine, respectively. However, the interpretation that the series of electron density peaks lining the groove represents indeed water molecules, while generally agreed upon, remains an assumption. The limited resolutions of dodecamer crystal structures hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
241
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(262 citation statements)
references
References 35 publications
19
241
2
Order By: Relevance
“…The magnitude of the effect is consistent with previous experimental results on the extent and location of NH 4 ϩ binding to A4T4, T4A4, and GCA5CG (53). The ApT step represents a unique and species-dependent tight binding site for monovalent cations, which can coordinate to the two opposing T carbonyls (41,(49)(50)(51)(52)(53)55). We propose that the specific minor groove widthdependent binding of monovalent cations at the ApT step contributes to the global bend observed for A4T4.…”
Section: Global Bend Of D(caaaattttg)n and D(gttttaaaac)nsupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitude of the effect is consistent with previous experimental results on the extent and location of NH 4 ϩ binding to A4T4, T4A4, and GCA5CG (53). The ApT step represents a unique and species-dependent tight binding site for monovalent cations, which can coordinate to the two opposing T carbonyls (41,(49)(50)(51)(52)(53)55). We propose that the specific minor groove widthdependent binding of monovalent cations at the ApT step contributes to the global bend observed for A4T4.…”
Section: Global Bend Of D(caaaattttg)n and D(gttttaaaac)nsupporting
confidence: 90%
“…X-ray crystallography (49,50), molecular dynamics (51), capillary electrophoresis (52), and NMR (53) studies of DNA have shown that, in addition to waters, monovalent cations can bind specifically in the minor groove of A-tracts, although the relative occupancies remain unresolved (54). In our previous NMR studies of A4T4 and T4A4, NH 4 ϩ were found to localize in the narrowest parts of the minor grooves, resulting in a very different distribution of cation localization for the two molecules that was proposed to contribute to A-tract bending (53).…”
Section: Global Bend Of D(caaaattttg)n and D(gttttaaaac)nmentioning
confidence: 99%
“…Such interactions between metal cations and nucleobases can be direct or solvent-mediated [21]. However, in the case of alkali metals, the X-ray investigations [22,23] and MD simulations [24] support mostly direct interactions between nucleobases and partially dehydrated metal ions [25]. Interactions with active centers of guanine located in major groove of DNA (N7 and O at C6 atom) have been discussed for years [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Since GC-rich sequences preferentially localize cations in the major groove (111)(112)(113)(114)(115)(116)(117) and undergo the B-to Α-form structural transition relatively easily (118)(119)(120)(121)(122), and Α-tract DNAs preferentially bind cations in the minor groove (57,58,107,109,(123)(124)(125) and have the relatively rigid B'-DNA structure (40, 41), Hud and coworkers (110) have proposed that DNA conformation is determined by the relative proportion of counterions preferentially localized in the major and minor grooves of GC-rich and Α-tract sequences, respectively. While much experimental data can be correlated by this hypothesis, it is possible that the ionophore concept may be more applicable to DNA and RNA structures that require counterion binding for stability.…”
Section: The Futurementioning
confidence: 99%
“…It is well known that DNA hydration is sequence dependent (126,127), although it is not often remembered that Aform DNA is stable up to 98% relative humidity and B-form DNA is stable down to 66% relative humidity (3). The "spine of hydration" on the floor of the DNA minor groove (9) appears to be covered by one or more layers of relatively well-ordered water molecules (57,58,106,116,124,128,129). The transient localization of cations on the floor of the minor groove must disrupt this ordered water structure, although how it happens is not clear (130).…”
Section: The Futurementioning
confidence: 99%